2016
DOI: 10.1016/j.yebeh.2016.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory stimulation induces delayed responses in epilepsy

Abstract: Precipitation and inhibition of seizures and epileptic discharges by sensory stimuli are receiving increasing attention because they provide insight into natural seizure generation in human epilepsies and can identify potential nonpharmacological therapies. We aimed to investigate modulation (provocation or inhibition) of epileptiform discharges (EDs) in mesial temporal lobe epilepsy (MTLE) versus idiopathic generalized epilepsy (IGE) by olfactory stimulation (OS) compared with standard provocation methods. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
6
15
0
1
Order By: Relevance
“…Taken together, the results of this study are associated to the multinational research consortium Epilepsies with External Modification of Ictogenesis ( EpExMo ), aimed at collaborating with the knowledge associated to basic mechanisms and clinical features of epilepsy inhibited or triggered by external sensory or cognitive stimuli. Our current experiments are in fact absolutely coherent with previous studies ( 7 , 8 , 15 18 , 20 , 57 , 90 – 92 ), adding consistent data to the literature. Furthermore, our findings certainly represent a partial component that will collaborate to the understanding of efficacy of odorants in the seizure response, with potential translational impact.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Taken together, the results of this study are associated to the multinational research consortium Epilepsies with External Modification of Ictogenesis ( EpExMo ), aimed at collaborating with the knowledge associated to basic mechanisms and clinical features of epilepsy inhibited or triggered by external sensory or cognitive stimuli. Our current experiments are in fact absolutely coherent with previous studies ( 7 , 8 , 15 18 , 20 , 57 , 90 – 92 ), adding consistent data to the literature. Furthermore, our findings certainly represent a partial component that will collaborate to the understanding of efficacy of odorants in the seizure response, with potential translational impact.…”
Section: Discussionsupporting
confidence: 92%
“…The latter report was strongly supported by our experimental findings, confirming the TOL anticonvulsant effects, in the acute and chronic (kindled) audiogenic seizures, in Wistar Audiogenic Rat (WAR) animals (18). Conversely, the induction of seizures by olfactory stimulation has also been reported, in both animal models and in the clinic (19)(20)(21)(22). In fact, the neurophysiological mechanisms of both anti-and pro-convulsant modulations are little understood.…”
Section: Introductionsupporting
confidence: 81%
“…At present, the neurophysiological mechanisms and the knowledge needed to understand epilepsy treatment with odorants are still unknown [29]. In that direction, our current findings add to the limited data of the literature which indicate that the olfactory stimulation modulates the epileptic activity, suppressing or inhibiting it [9,10,20,[26][27][28][29][30][31][32]43].…”
Section: Discussionmentioning
confidence: 87%
“…The involvement of olfactory structures with TLE is known for quite some time [20,21]. Some studies have shown that olfactory sensations could indicate the paroxystic seizure onset in patients with TLE, a symptom described as aura [20][21][22][23][24], and that the peripheral sensory stimulation, such as an olfactory stimulus is able to modulate those seizures: suppressing or inhibiting [9,10,20,[25][26][27][28][29][30][31][32] or even inducing them, such as in the reflex epilepsies [29,[33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent systematic investigation of the effect of olfactory stimuli on epileptiform EEG discharge revealed delayed responses in the minutes following exposure to an aromatic smell in about one-half of the patients. These responses were bi-directional (14): in IGE, they were inhibitory twice as often as excitatory, whereas in TLE, the relation was the reverse (40).…”
Section: Sensory Systems In Ictogenesismentioning
confidence: 99%